MANAJEMAN PERUBAHAN DI LINGKUNGAN SEKOLAH PADA IMPLEMENTASI KEPEMIMPINAN VISIONER DALAM MEWUJUDKAN KUALITAS PENDIDIKAN DIGITAL DI SDN KERSIKAN I BANGIL - Inul Zulzila; Suyanto; A. Faizin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research aims to describe and analyze change management in the school environment in the implementation of visionary leadership to realize the quality of digital education at SDN Kersikan I Bangil. Changes in the world of education require leadership that is able to adapt to technological developments and the digitalization of learning. Principals as visionary leaders play an important role in creating a vision, strategy, and school culture that supports sustainable digital transformation. This study uses a qualitative approach with a descriptive method. The research subjects include school principals, teachers, and education staff at SDN Kersikan I Bangil. Data was obtained through interviews, observations, and documentation, then analyzed through the stages of data reduction, data presentation, and conclusion drawn. The results of the study show that change management at SDN Kersikan I Bangil is carried out through the stages of planning, implementation, and targeted evaluation with the support of the visionary leadership of the principal. School principals play a role as drivers of digital innovation, motivators, as well as facilitators in improving teacher competence and digital infrastructure facilities. Supporting factors for success include collaboration between school residents, government support, and joint commitment in realizing quality digital education. The implications of this study show that the implementation of change management based on visionary leadership is able to increase the effectiveness of digital learning, strengthen innovative culture in schools, and support the realization of quality education that is relevant to the demands of the 21st century